Pengamatan Pengendalian Bahaya H2S di Central Processing Plant PT XYZ - Surendra, Daffa Ariella; Sikam, Annisa Aulia; Imantaka, Christopher Audi; Widodo, Najwa Kamila (Jurnal Migasian, 2024)
PT XYZ processes natural gas of the associated gas type where for this type, natural gas is found together consisting of 8 wells. It cannot be denied, that in the process of oil and gas production, there will certainly be some dangerous contaminants that are included and can threaten the safety of workers and the environment. One of the dangerous examples is H₂S. H₂S is a toxic gas that is colorless, smells pungent like rotten eggs, and has a density that is heavier than air. The content of Hydrogen Sulfide (H₂S) is very dangerous for the environment and detrimental to producers because of its corrosive properties that can damage equipment. In addition to damaging equipment, Hydrogen Sulfide (H₂S) is also harmful to human health due to its toxic nature. If the Hydrogen Sulfide (H₂S) content exceeds the Threshold Value (NAB) of 10 ppm and is exposed to humans, it will cause loss of consciousness until death. The data collection method used by the author in preparing this article is through discussions (interviews), literature studies, and field orientation. Based on the environmental quality standard value set by Permenakertrans Number PER.13/MEN/X/2011 which is 1 ppm.